Mild iron deficiency does not ameliorate the phenotype of a murine erythropoietic protoporphyria model. Issue 5 (7th February 2020) - Schmidt, Paul J.; Hollowell, Monica L.; Fitzgerald, Kevin; Butler, James S.; Fleming, Mark D.
Abstract: Reduced ferrochelatase activity in erythropoietic protoporphyria (EPP) causes the accumulation of protoporphyrin IX (PPIX) leading to acute cutaneous photosensitivity and liver injury. Many EPP patients also have a mild hypochromic, microcytic anemia and iron deficiency. Iron deficiency can lead to decreased PPIX accumulation in another erythropoietic porphyria, congenital erythropoietic porphyria (CEP). Expression of the iron regulatory peptide hepcidin is negatively regulated by the serine protease TMPRSS6 . Hepcidin induction by siRNA‐mediated inhibition of TMPRSS6 expression reduces iron availability and induces iron deficiency. To interrogate the therapeutic potential of iron deficiency to modify EPP, we treated an ethylnitrosourea‐induced mouse model of EPP, Fech m1Pas, with a GalNAc ‐ conjugated Tmprss6 siRNA and PPIX levels, anemia and iron parameters were monitored. The GalNAc‐RNAi therapeutic reduces Tmprss6 expression and induces mild iron deficiency in Fech m1Pas animals. However, decreases in erythrocyte PPIX levels and liver PPIX accumulation were not seen. These results indicate short‐term induction of iron deficiency, at least in a murine model of EPP, does not lead to decreased PPIX production.